Building Leadership Relationships Online - Molzer, Abigaile I. (My University, 2020)
LEAD 212: Introduction to Leadership Concepts, is the first course associated with the popular Leadership Studies minor held in the Staley School of Leadership Studies at Kansas State University. As a program built around the leadership premise that leadership is a relationship, in-person courses emphasize student engagement amongst each other and with instructors. The COVID-19 pandemic forced courses initially held in-person to be shifted to online platforms only, creating significant challenges. A literature review exploring the importance of teacher-student relationships in higher education, online learning in higher education, and a glimpse into emerging literature on the effects of education caused by COVID-19 share information that be influential in future adaptations of online courses. Studies exposing the need for educators to provide extensive personal and academic care and strategies for approachability connected closely with the positive impact that both learning communities and peer mentors can have on student satisfaction (Denzine & Pulos 2000) (Hurd & Stein 2004) (Kuh et al. 2008). Online platforms are increasingly important in creating space for social engagement in online courses, as well as the various roles that instructors must take on (Salmon 2000). Additionally, personal accounts based on experience as a class leader for the spring 2020 LEAD 212 create a foundation for supplemental material to provide future class leaders in preparation for another semester of online leadership curriculum.